The prevalence and distribution of the amyloidogenic transthyretin (TTR) V122I allele in Africa. Issue 5 (14th July 2016) - Jacobson, Daniel R.; Alexander, Alice A.; Tagoe, Clement; Garvey, W. T.; Williams, Scott M.; Tishkoff, Sara; Modiano, David; Sirima, Sodiomon B.; Kalidi, Issa; Toure, Amadou; Buxbaum, Joel N.
Abstract: Background: Transthyretin (TTR) pV142I (rs76992529‐A) is one of the 113 variants in the human TTR gene associated with systemic amyloidosis. It results from a G to A transition at a CG dinucleotide in the codon for amino acid 122 of the mature protein (TTR V122I). The allele frequency is 0.0173 in African Americans. Methods: PCR‐based assays to genotype 2767 DNA samples obtained from participants in genetic studies from various African populations supplemented with sequencing data from 529 samples within the 1000 Genomes Project. Results: The rs76992529‐A variant allele was most prevalent (allele frequency 0.0253) in the contiguous West African countries of Sierra Leone, Guinea, Ivory Coast, Burkina Faso, Ghana, and Nigeria. In other African countries, the mean allele frequency was 0.011. Conclusions: Our data are consistent with a small number of founder carriers of the amyloidogenic TTR V122I (p.Val142Ile) allele in southern West Africa, with no apparent advantage or disadvantage of an allele carrying newborn reaching adulthood. In U.S. African Americans, the allele represents a significant risk for congestive heart failure late in life. If clinical penetrance is similar in African countries with high allele frequencies, then cardiac amyloidosis could also represent a significant cause of heart disease in the elderly in those populations. Abstract : The substitution of isoleucine for valine at position 122 in the human protein transthyretin makes it subject to amyloid formation in vivo. The allele is found in 3.4 % of African Americans producing cardiac disease in many of the carriers late in life. The present study defines its prevalence across the African continent and shows the highest concentration in countries of West Africa, a small number of founders, and no apparent selective advantage or disadvantage in reaching adulthood.